Penerapan Metode Ward and Peppard dalam Perencanaan Strategi Sistem Informasi pada PT Athria Cipta Mandiri - Syeira Khaerani; Arif Yulianto (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to formulate an information system strategic planning model for PT Athria Cipta Mandiri using the Ward and Peppard method. The research was conducted because the company still faces several problems in managing tender and construction project data, such as unintegrated systems between divisions, semi-digital administrative processes, repeated data input, the absence of a centralized database, and project reporting that has not been carried out in real time. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and literature study. The analysis was conducted using Value Chain, PESTEL, SWOT, Critical Success Factor, McFarlan Strategic Grid, and application portfolio recommendations. The results show that PT Athria Cipta Mandiri needs an integrated information system for tender and project management, web-based project reporting and monitoring, a document management system, business intelligence dashboard, centralized cloud database, and stronger IT governance. The proposed strategy is expected to improve operational efficiency, data accuracy, inter-division coordination, and data-based managerial decision making.